Act early to prevent infections and save lives: causal impact of diagnostic efficiency on the COVID-19 pandemic - Chen, Simiao; Jin, Zhangfeng; Bloom, David E. (Discussion paper series, 2020)
This paper examines the impact of diagnostic efficiency on the COVID-19 pandemic. Using an exogenous policy on diagnostic confirmation, we show that a one- day decrease in the time taken to confirm the first case in a city publicly led to 9.4% and 12.7% reductions in COVID-19 prevalence and mortality over the subsequent six months, respectively. The impact is larger for cities that are farther from the COVID-19 epicenter, are exposed to less migration, and have more responsive public health systems. Social distancing and a less burdened health system are likely the underlying mechanisms, while the latter also explains the more profound impact on reducing deaths than reducing infections.
Keywords: Graue Literatur